Environment - Elliott, Deborah (Wayland Hove, 1993)
"Environment" by Deborah Elliott, published in 1993, is part of the "Into Europe" series. This 48-page book explores various European environments and the measures being taken to ensure their preservation. It is illustrated throughout in color.